Difference between revisions of "009A Sample Final 1, Problem 7"

From Math Wiki
Jump to navigation Jump to search
 
(2 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
<span class="exam">A curve is defined implicitly by the equation
 
<span class="exam">A curve is defined implicitly by the equation
  
::::::<math>x^3+y^3=6xy.</math>
+
::<math>x^3+y^3=6xy.</math>
  
<span class="exam">a) Using implicit differentiation, compute &thinsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>.
+
<span class="exam">(a) Using implicit differentiation, compute &nbsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>.
  
<span class="exam">b) Find an equation of the tangent line to the curve <math style="vertical-align: -4px">x^3+y^3=6xy</math> at the point <math style="vertical-align: -5px">(3,3)</math>.
+
<span class="exam">(b) Find an equation of the tangent line to the curve &nbsp;<math style="vertical-align: -4px">x^3+y^3=6xy</math>&nbsp; at the point &nbsp;<math style="vertical-align: -5px">(3,3)</math>.
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|'''1.''' What is the result of implicit differentiation of <math style="vertical-align: -4px">xy?</math>
+
|'''1.''' What is the result of implicit differentiation of &nbsp;<math style="vertical-align: -4px">xy?</math>
 
|-
 
|-
 
|
 
|
::It would be&thinsp; <math style="vertical-align: -13px">y+x\frac{dy}{dx}</math>&thinsp; by the Product Rule.
+
&nbsp; &nbsp; &nbsp; &nbsp; It would be &nbsp;<math style="vertical-align: -13px">y+x\frac{dy}{dx}</math>&nbsp; by the Product Rule.
 
|-
 
|-
 
|'''2.''' What two pieces of information do you need to write the equation of a line?
 
|'''2.''' What two pieces of information do you need to write the equation of a line?
 
|-
 
|-
 
|
 
|
::You need the slope of the line and a point on the line.
+
&nbsp; &nbsp; &nbsp; &nbsp; You need the slope of the line and a point on the line.
 
|-
 
|-
 
|'''3.''' What is the slope of the tangent line of a curve?
 
|'''3.''' What is the slope of the tangent line of a curve?
 
|-
 
|-
 
|
 
|
::The slope is&thinsp; <math style="vertical-align: -13px">m=\frac{dy}{dx}.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; The slope is &nbsp;<math style="vertical-align: -13px">m=\frac{dy}{dx}.</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 33: Line 34:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Using implicit differentiation on the equation&thinsp; <math style="vertical-align: -4px">x^3+y^3=6xy,</math> we get
+
|Using implicit differentiation on the equation &nbsp;<math style="vertical-align: -4px">x^3+y^3=6xy,</math>&nbsp; we get
 
|-
 
|-
 
|
 
|
::<math>3x^2+3y^2\frac{dy}{dx}=6y+6x\frac{dy}{dx}.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>3x^2+3y^2\frac{dy}{dx}=6y+6x\frac{dy}{dx}.</math>
 
|}
 
|}
  
Line 42: Line 43:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we move all the &thinsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&thinsp; terms to one side of the equation.
+
|Now, we move all the &nbsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&nbsp; terms to one side of the equation.
 
|-
 
|-
 
|So, we have
 
|So, we have
 
|-
 
|-
 
|
 
|
::<math>3x^2-6y=\frac{dy}{dx}(6x-3y^2).</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>3x^2-6y=\frac{dy}{dx}(6x-3y^2).</math>
 +
|-
 +
|We solve to get
 
|-
 
|-
|We solve to get &nbsp;<math style="vertical-align: -17px">\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -17px">\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}.</math>
 
|}
 
|}
  
Line 57: Line 60:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we find the slope of the tangent line at the point &thinsp;<math style="vertical-align: -5px">(3,3).</math>
+
|First, we find the slope of the tangent line at the point &nbsp;<math style="vertical-align: -5px">(3,3).</math>
 
|-
 
|-
|We plug  <math style="vertical-align: -5px">(3,3)</math>&thinsp; into the formula for &thinsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&thinsp; we found in part '''(a)'''.
+
|We plug  &nbsp;<math style="vertical-align: -5px">(3,3)</math>&nbsp; into the formula for &nbsp;<math style="vertical-align: -12px">\frac{dy}{dx}</math>&nbsp; we found in part (a).
 
|-
 
|-
 
|So, we get
 
|So, we get
 
|-
 
|-
 
|
 
|
::<math>m\,=\,\frac{3(3)^2-6(3)}{6(3)-3(3)^2}\,=\,\frac{9}{-9}\,=\,-1.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 +
\displaystyle{m} & = & \displaystyle{\frac{3(3)^2-6(3)}{6(3)-3(3)^2}}\\
 +
&&\\
 +
& = & \displaystyle{-\frac{9}{9}}\\
 +
&&\\
 +
& = & \displaystyle{-1.}
 +
\end{array}</math>
 
|}
 
|}
  
Line 70: Line 79:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we have the slope of the tangent line at <math style="vertical-align: -5px">(3,3)</math>&thinsp; and a point.  
+
|Now, we have the slope of the tangent line at &nbsp;<math style="vertical-align: -5px">(3,3)</math>&nbsp; and a point.  
 
|-
 
|-
 
|Thus, we can write the equation of the line.
 
|Thus, we can write the equation of the line.
 
|-
 
|-
|So, the equation of the tangent line at <math style="vertical-align: -5px">(3,3)</math>&thinsp; is  
+
|So, the equation of the tangent line at &nbsp;<math style="vertical-align: -5px">(3,3)</math>&nbsp; is  
 
|-
 
|-
 
|
 
|
::<math>y\,=\,-1(x-3)+3.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>y\,=\,-1(x-3)+3.</math>
|-
 
||[[File: 9AF1_7_GP.png |center|450px]]
 
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|'''(a)'''&thinsp; <math>\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}</math>
+
|&nbsp; &nbsp; '''(a)'''&nbsp; &nbsp; <math>\frac{dy}{dx}=\frac{3x^2-6y}{6x-3y^2}</math>
 
|-
 
|-
|'''(b)'''&thinsp; <math>y=-1(x-3)+3</math>
+
|&nbsp; &nbsp; '''(b)'''&nbsp; &nbsp; <math>y=-1(x-3)+3</math>
 
|}
 
|}
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:13, 10 April 2017

A curve is defined implicitly by the equation

(a) Using implicit differentiation, compute  .

(b) Find an equation of the tangent line to the curve    at the point  .

Foundations:  
1. What is the result of implicit differentiation of  

        It would be    by the Product Rule.

2. What two pieces of information do you need to write the equation of a line?

        You need the slope of the line and a point on the line.

3. What is the slope of the tangent line of a curve?

        The slope is  


Solution:

(a)

Step 1:  
Using implicit differentiation on the equation    we get

       

Step 2:  
Now, we move all the    terms to one side of the equation.
So, we have

       

We solve to get
       

(b)

Step 1:  
First, we find the slope of the tangent line at the point  
We plug    into the formula for    we found in part (a).
So, we get

       

Step 2:  
Now, we have the slope of the tangent line at    and a point.
Thus, we can write the equation of the line.
So, the equation of the tangent line at    is

       


Final Answer:  
    (a)   
    (b)   

Return to Sample Exam